2010
DOI: 10.1254/jphs.10033fp
|View full text |Cite
|
Sign up to set email alerts
|

CV-159, a Unique Dihydropyridine Derivative, Prevents TNF-Induced Inflammatory Responses in Human Umbilical Vein Endothelial Cells

Abstract: Abstract. CV-159, a 1,4-dihydropyridine derivative, has Ca 2+ antagonistic and anti-calmodulin actions. An early feature of atherosclerosis is vascular endothelial inflammatory change. We examined whether CV-159 has protective effects against endothelial inflammatory responses. After pretreatment of human umbilical vein endothelial cells (ECs) with CV-159 (10 μ M, 30 min), TNF-α (10 ng/ml) was applied for 20 min or 24 h. Expressions of inflammatory markers and activation of inflammatory signal molecules were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…In the previous study, we showed that an antioxidant drug, N-acetyl l-cysteine inhibited TNF-induced expression of VCAM-1 and e-selectin, as well as activation of Akt, JNK, and p38, in cultured SMCs or endothelial cells. 14,15 In addition, we confirmed that the inhibitor of Akt, JNK, or p38 prevented TNF-induced expression of VCAM-1 or e-selectin. Collectively, our results indicate that DAPK3 mediates TNFinduced inflammation via induction of proinflammatory molecules (VCAM-1, e-selectin, and COX-2) through activation of ROS-dependent signals in cultured SMCs and endothelial cells.…”
Section: October 2012supporting
confidence: 66%
“…In the previous study, we showed that an antioxidant drug, N-acetyl l-cysteine inhibited TNF-induced expression of VCAM-1 and e-selectin, as well as activation of Akt, JNK, and p38, in cultured SMCs or endothelial cells. 14,15 In addition, we confirmed that the inhibitor of Akt, JNK, or p38 prevented TNF-induced expression of VCAM-1 or e-selectin. Collectively, our results indicate that DAPK3 mediates TNFinduced inflammation via induction of proinflammatory molecules (VCAM-1, e-selectin, and COX-2) through activation of ROS-dependent signals in cultured SMCs and endothelial cells.…”
Section: October 2012supporting
confidence: 66%
“…For example, it was reported that azelnidipine inhibited TNF-induced NF-κ B activation and VCAM-1 expression by the inhibition of ROS in human aortic endothelial cells (ECs) (30). Our previous study demonstrated that CV-159 inhibits TNF-induced expression of e-selectin but not VCAM-1 via suppressing the activation of JNK, p38, and NF-κ B in vascular ECs (14). We also demonstrated that CV-159 prevents activation of JNK and p38 through inhibition of ROS, while it prevents activation of NF-κ B (p65) in a ROS-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular inflammatory responses represent a pathogenic feature of atherosclerosis, which is one of the major risk factors for ischemic cardiovascular disorders (10 -13). In an earlier study, we have demonstrated that CV-159 is protective against vascular endothelial inflammatory responses (14). Vascular smooth muscle cells (SMCs) proliferation and migration are also important features for the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (ECs) (HUVECs) were obtained from Kurabo (Osaka, Japan) and cultured in Medium 200 supplemented with low serum growth supplement (Cascade Biologics, Portland, OR) as described previously (39). Cells at passage from 3 to 10 were used.…”
Section: Methodsmentioning
confidence: 99%